أحكام المرآة في اليهودية والمسيحية دراسة موضوعية - بالرابح, سناء; زغدي, سليمة; حميد, شيماء (جامعة الوادي university of eloued, 2018)
This study addresses an important aspect and a major doctrinal theme in the Jewish and Christian Sharia, namely, the provisions on women in both of these religions, explaining what they had decided in their sources on the subject, in several provisions such as betrothal, marriage, divorce, adultery, inheritance and veil.... There appears to be a distinct difference between these two religions in the provisions on these issues by women, although Christianity is in its own right as a supplement to the Jewish religion.
مقارنة اديان